The epidemiology of multiple primary cancers in Belgium (2004–2017): Incidence, proportion, risk, stage and impact on relative survival estimates - Gilles Macq; Geert Silversmit; Freija Verdoodt; Liesbet Van Eycken (BMC Cancer, 2023)
Abstract Background As both life expectancy and cancer survival improve, the incidence of multiple primary cancer has augmented and is expected to further increase. This study describes for the first time the epidemiology of multiple invasive tumours in Belgium. Methods This nationwide study, based on all cancers diagnosed between 2004 and 2017 in Belgium, describes the proportion of multiple primary cancer, its evolution over time, the impact of inclusion or exclusion of multiple primary cancer on relative survival estimates, the risk of developing a second primary cancer, and the difference in stage between first and second primary cancer for the same patient. Results The proportion of multiple primary cancer increases with age, varies across cancer sites (from 4% for testis cancer to 22.8% for oesophageal cancer), is higher in men than in women, and has linearly increased over time. The inclusion of multiple primary cancer resulted in smaller 5-year relative survival and this impact is more pronounced in cancer sites with high relative survival. Patients with a first primary cancer have an increased risk to develop a new primary cancer compared to the population without a previous cancer history (1.27 and 1.59 times higher in men and women, respectively) and this risk depends on cancer site. Second primary cancers are associated with more advanced stages and more unknown stages than the corresponding first cancer diagnosis. Conclusions This study describes multiple primary cancer according to several measures (proportion, standardised incidence ratio for an second primary cancer, impact of multiple primary cancer on relative survival and differences according to stage) for the first time in Belgium. The results are based on data of a population-based cancer registry with a relatively recent onset (2004).